2012
DOI: 10.1159/000333447
|View full text |Cite
|
Sign up to set email alerts
|

<i>Staphylococcus aureus</i> Secretes Coagulase and von Willebrand Factor Binding Protein to Modify the Coagulation Cascade and Establish Host Infections

Abstract: Clinical isolates of Staphylococcus aureus secrete coagulases, polypeptides that bind to and activate prothrombin, thereby converting fibrinogen to fibrin and promoting the clotting of plasma or blood. Two staphylococcal products, the canonical coagulase (Coa) as well as the recently identified von Willebrand factor binding protein (vWbp), promote similar modifications of the coagulation cascade during host infection. Staphylococcal binding to fibrinogen or fibrin is an important attribute of disease pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
131
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(131 citation statements)
references
References 133 publications
(92 reference statements)
0
131
0
Order By: Relevance
“…This Gram-positive bacterium evolved to clot animal and human plasma, bind fibrinogen, and agglutinate within a meshwork of fibrin fibrils (3). S. aureus agglutination requires two secreted products, Coa (coagulase) and vWbp (von Willebrand factor-binding protein) (4), which each associate with and activate prothrombin to convert fibrinogen to fibrin (5,6).…”
mentioning
confidence: 99%
“…This Gram-positive bacterium evolved to clot animal and human plasma, bind fibrinogen, and agglutinate within a meshwork of fibrin fibrils (3). S. aureus agglutination requires two secreted products, Coa (coagulase) and vWbp (von Willebrand factor-binding protein) (4), which each associate with and activate prothrombin to convert fibrinogen to fibrin (5,6).…”
mentioning
confidence: 99%
“…staphylothrombin (21). Coagulase is thought to be responsible for the virulence of S. aureus (22). SSL10 did not inhibit the proteolytic activity of staphylothrombin, mildly attenuated the formation of staphylothrombin, and inhibited plasma clotting induced by coagulase.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, it was shown that the S. aureus protease staphopain A degrades SP-A, thus compromising host defense of the alveoli [5]. In a recent review, the importance of staphylococcal coagulases was discussed [6]. The canonical coagulase as well as the von Willebrand factor binding protein modify the coagulation cascade during infection.…”
mentioning
confidence: 99%